SUFISM AS SCIENTIA SACRA ACTUALIZED IN TRADITION AND RELIGION (PERSPECTIVE OF SAYYED HOSSEIN) - Zairotus Sholikah (UIN Walisongo Semarang, 2023)
Spiritual crises often occur in today's modern society which is trapped in human modernity. This gap results in a lack of divine knowledge (perennialism) which is in human nature. This study is intended to answer the question How is the relation of Sufism as sacred knowledge embodied in religion and tradition. This research is a qualitative research with a philosophical approach. The research location as a source of data through interviews, participant observation, and documentation. All data were analyzed using the concepts of knowledge and holiness Sayyed Hossein Nasr with scientia sacra knowledge. This study shows that perennialism and Sufism have a relationship in explaining the purpose and nature of religion, namely